Peningkatan Kualitas Sumber Daya Insani Pada Lembaga Keuangan Syariah - Suhairi, Suhairi; Siregar, Risma Haryani; Sibagariang, Yola Aprilia; Astri, Yulita; Lubis, Yulpida Sari (LPPM Universitas Labuhanbatu, 2023)
The purpose of this study is to explain how to improve the quality of Human Resource Management (SDI) in Sharia financial institutions. The Islamic economy in Indonesia today has undergone substantial development. Unfortunately, the development of these is not balanced by the qualified human resources. Human Resources power is one of the problems faced by the Institute of Sharia recurrence.Using an approach using the literature review approach, which the author is looking for relevant discussion used with study taken from several related articles with human resources management (human).From the results of the can be inferred that to improve the quality managementmen human resources (human) on Sharia financial institutions required training, development, and education on things that relate to the source of human power (human) that is enforced in Sharia institutions and the enactment of certification because if there is no shows the lapse of birth in the field that leads to compete in the era of globalization.